PERILAKU SISWA DALAM PEMBELAJARAN MENGGUNAKAN INTERNET SEBAGAI MEDIA BELAJAR (STUDI DI SEKOLAH MENENGAH ATAS NEGERI 2 SUNGAI AMBAWANG) - Sikwan, Agus; Syarmiati, Syarmiati; Utami, Silsilia Esti (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This research aims to describe students"™ behavior in using the internet while learning and analyze factors that change the students"™ behavior at the State Senior High School 2 of Sungai Ambawang. The research used a qualitative method to obtain a detailed and comprehensive understanding of their behavior using the internet as learning media at school. The research found that the student struggled to concentrate during the lesson. One of the factors was that the students played game, browsed other media, and did other online activities. The data were collected using interviews, observation, and documentation. To analyze the data, the researchers did several procedures such as data reduction, presentation, and verification. This research used a behaviorism theory expressed by B.F. Skinner. This theory focuses on the relationship between the effect of an individual"™s behavior on his surroundings and the effect of the surrounding on the individual. According to Skinner, almost all human behavior falls into two categories: respondent and operant behavior. Respondent behavior is an unconscious action (reflex) that is resulted from a particular stimulus from the surrounding. Meanwhile, the operant behavior refers to behavior emitted spontaneously and freely.